Coconuts placed in a Kalash - Mumbai Archive Project Team (Jio Institute, 2024)
Individual families bring coconuts to Versova Beach by placing them in a kalash (pot) and carrying the pot on their heads. Though Narali Purnima is primarily a festival observed by sea-faring fishing communities, other communities also offer coconuts to the sea on this auspicious occasion.